Renewable Oil Extracted from Indonesian Srikaya’s (Annona squamosa sp.) Seed: Another Potent Source for Biodiesel - Masruri Masruri; Mukesh Sharma; Warsito Warsito; Prasetyo Adi (Chemistry Department, The University of Brawijaya, 2012)
This study looks at the wastes derived from Indonesian fruit as prospect for biofuels. This report investigates the chemical composition of Srikaya (Annona squamosal sp.) seed, which is disposed as waste products from traditional markets. The seeds were extracted with various extraction methods and the oil obtained was analysed by means of gas chromatography (GC/FID), gas chromatography-mass spectrometry (GC/MS), infra-red spectrometry and ultra-violet-visible spectrometry. It was found 2 h extraction using soxhlet apparatus with diethyl ether as solvent gave the optimum time extraction. Moreover, five major components were isolated from i.e.: ethyl hexadecanoate, ethyl hexadec-9-enoate, ethyl octadecanoate, 2-hydroxy-1,3-propanediyl hexadecanoate, octadec-9-enaldehyde, and unknown compound, respectively.